Kinematic changes in 5-m swimming start performance using the new double kick start block - Matúš, I.; Eliaš, T.; Vadašová, B.; Czarny, W.; Rydzik, L.; Ambrozy, T.; Szczypka, K.; Ružbarský, P. (Frontiers in Sports and Active Living, 2025)
Enhancing start performance can substantially reduce overall race time, particularly in sprint swimming events. The aim of this study was to examine differences in angular and temporal characteristics of individual start phases over 5 m when performing from the new DKS ("double kick start") starting block in various pedal angle settings and from the OSB12 starting platform. The sample consisted of 13 junior competitive swimmers (age 17.7 ± 1.1 years), who completed a total of 10 maximal-effort starts. From the DKS block, swimmers performed two attempts at pedal settings of 30°/30°, 40°/40°, 50°/50°, and 60°/60°, and two attempts from the OSB12 platform. Kinematic parameters above and below the water surface were analyzed using a 4-camera SwimPro system and Dartfish ProSuite 4.0 software. Differences between conditions were evaluated using repeated measures ANOVA. For significant interactions, post hoc LSD analysis was applied, and effect sizes were determined by partial eta squared. Results showed that the DKS block with 40°/40° and 50°/50° pedal settings enabled junior performance swimmers to execute significantly more effective starts compared to the OSB12 platform (p < .001, Etap² = 0.78-0.90). Improvements were most evident in shorter block time (0.62 ± 0.04-0.06 s vs. 0.78 ± 0.01 s), enhanced flight phase parameters (shorter flight time and greater flight distance; p < .001), and faster 5-m times (1.44 ± 0.06-0.08 s vs. 1.70 ± 0.03 s; p < .001). Our findings suggest that the use of variable pedal angles on the new DKS starting block significantly improves start kinematics and positively affects 5-m performance, which may contribute to optimizing swimmers` overall performance in the initial phase of the race.